Estimated daily intake of phenolics and antioxidants from green tea consumption in the Korean diet. (2nd April 2016) - Lee, Bong Han; Nam, Tae Gyu; Park, Na Young; Chun, Ock K.; Koo, Sung I.; Kim, Dae-Ok
Abstract: To estimate daily intake of total phenolics and flavonoids from green tea and the contribution of green tea to the antioxidant intake from the Korean diet, 24 commercial brands of green tea were selected and analyzed. Data from the Korea National Health and Nutrition Examination Survey (KNHANES) from 2008 and 2011 indicate that the green tea consumption in these 2 years was 2.8 g/tea drinker/day and 2.9 g/tea drinker/day, respectively. Based on data derived from direct measurements of green tea phenolics and the dataset of the 2008 KNHANES, we estimated the daily per tea drinker phenolics intake to be 172 mg gallic acid equivalents (GAE), the total flavonoids to be 43 mg catechin equivalents (CE) and the total antioxidants to be 267 mg vitamin C equivalents (VCE; 1, 1-diphenyl-2-picrylhydrazyl (DPPH) assay) and 401 mg VCE (2, 2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) assay). In 2011, we estimated the daily per tea drinker total phenolics intake to be 246 mg GAE, the total flavonoids to be 60 mg CE and the antioxidants to be 448 mg VCE (DPPH assay) and 630 mg VCE (ABTS assay). The daily intake of total phenolics, total flavonoids and antioxidants from green tea consumption increased from 2008 to 2011.